Development and Psychometric Evaluation of Traffic-related Pre-hospital Mortality Prevention Questionnaire - Davoud Khorasani-Zavareh; Abbasali Dehghani Tafti; Khadijeh Nasiriani; Majid Hajimaghsoudi; Hossien Fallahzadeh; Adel Eftekhari (Gonabad University of Medical Sciences, 2023)
Background: Since a significant part of deaths due to traffic accidents are preventable in the pre-hospital phase, therefore it seems necessary to have an instrument to identify and measure the factors affecting it. This study aims to develop and psychometrically assess an instrument to measure preventable prehospital mortality due to traffic accidents. Methods: The study is a mixed qualitative-quantitative study, including systematic review, interviews, Delphi, and psychometrics. In the systematic review phase, using database searches, and in the qualitative phase, the factors affecting preventable mortality were extracted via interviews with 24 experts (fire-fighting organizations, traffic police, the Red Crescent, emergency medical services [EMS], emergency medicine, hospital emergency nurses and traffic accident victims) in Ministry of Health, Treatment and Medical Education and Yazd Province, Iran, 2020. The codes were classified with MAXQDA10 Software. The results were collected in the format of the primary instrument and the Delphi study (3 rounds) was conducted by experts. Finally, the reduction of the items and the psychometrics of the instrument, including the determination of face and content validity, and then the determination of the reliability using Cronbach's alpha were performed. Results: The developed instrument had acceptable validity and reliability to be used in measuring preventable traffic-related pre-hospital mortalities. The final instrument to measure preventable pre-hospital mortality was developed with 5 dimensions, including "scene and casualty assessment, coordination and communication, time management, training performance, and support".  Conclusion: Using this instrument, preventable deaths can be detected, the present challenges can be identified, and the preventable deaths may be diminished.